Development of a UV−Vis Spectroscopy Method Allied with Chemometrics for Simultaneous Analysis of Dexketoprofen Trometamol and Thiocolchicoside in Commercial Tablets - Öncel, Nilay; Dal, Sema Nur; Çeçen, Selen Duygu; Arslan, Fatma Nur (Trends in Pharmacy, 2025)
Background: Herein, a simple UV–Vis spectrophotometric method coupled with che mometrics including principal component analysis (PCA) and partial least squares (PLS) regression/prediction analysis was utilized for the simultaneous determina tion of dexketoprofen trometamol (DEX) and thiocolchicoside (TCC) in their binary pharmaceutical dosages. Methods: Different binary dosages of DEX and TCC at known concentrations were prepared via the central composite experimental design methodology. The UV–Vis spectra of pharmaceutical sets were recorded in the spectral region of 200-800 nm, and with the help of these data, the chemometrics models were cre ated with Unscambler X10.4 software. Full cross-validation strategy and NIPALS algorithms were applied to evaluate the performance of models in terms of accu racy and predictive abilities. Results: The PCA models showed statistically successful findings with high eigen values. The values of R2, RMSEC and RMSECV were found to be 0.9939, 0.0028 and 0.0033 mg for TCC, respectively, by PLS regression. The R², RMSEC, and RMSECV were obtained for DEX as 0.9939, 0.0036, and 0.0048 mg, respectively. The R², RMSEC, and RMSECV were obtained for the binary mixtures of DEX and TCC as 0.9901, 0.0042, and 0.0051 mg, respectively. Lastly, the commercial pharmaceuti cal tablets including DEX and TCC ingredients were tested with high prediction abilities. Conclusion: The developed UV–Vis method allied with chemometrics enables more sensitive and cost–effective measurement for the simultaneous determination of DEX and TCC. The method could be applied for quality control analysis of many pharmaceutical preparations. Cite this article as: Öncel N, Dal SN, Çeçen SD, Arslan FN. Development of a UV−vis spectroscopy method allied with chemometrics for simultaneous analysis of dexketoprofen trometamol and thiocolchicoside in commercial tablets. Trends in Pharmacy, 2025, 2, 0021, doi: 10.5152/TrendsPharm.2025.25021.